Do we need sutureless or self-anchoring aortic valve prostheses? - Shrestha, Malakh (Annals of Cardiothoracic Surgery, 2014)
Surgical aortic valve replacement (AVR) is the ‘gold standard’ for the treatment of aortic valve stenosis. Due to increasing age of the patient population (reflecting the demographic changes), the use of biological valves has increased over the past years. At the same time, a large proportion of these patients require concomitant surgical procedures in addition to AVR. Although trans-apical or trans-femoral aortic valve implantations (TAVI) have been introduced for high risk patients, they are limited to patients with isolated aortic valve pathology. Therefore, concepts of aortic valve replacement avoiding long ischemia times, as well as long periods of extra-corporeal circulation (ECC) resulting in reduced peri-operative risks should be welcomed among the surgical community. Modern ‘sutureless valves’ with reduced X-clamp and cardio-pulmonary bypass times as a result of the absence of sutures, combined with excellent hemodynamics in the short and mid-term may be an ideal solution for geriatric patients. Additionally, ‘self-anchoring’ valves will increase the armament of surgeons in treating ‘technically difficult’ group of patients needing AVR with small calcified aortic roots and those coming back after aortic root replacement with homografts. These valves should also help in increasing wider application of minimally access AVR. Therefore, the question of whether we need ‘self-anchoring valves’ is not only redundant, but the time may have come for these type of valves to be considered as the ‘valve of choice’ for higher risk geriatric patients who may be ‘high risk’ for conventional valves but not ‘high risk enough’ or ineligible for TAVIs.